2021
DOI: 10.1016/j.celrep.2021.109348
|View full text |Cite
|
Sign up to set email alerts
|

Glucose- and sucrose-signaling modules regulate the Arabidopsis juvenile-to-adult phase transition

Abstract: Highlights d CINV1/2 are key endogenous factors that control the Arabidopsis juvenile-to-adult transition d A glucose-signaling feed-forward loop dynamically controls the juvenile-to-adult transition d A sucrose-signaling pathway regulates the juvenile-to-adult transition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The cotyledon greening of etiolated seedlings was promoted by endogenous sugars Cytosolic invertase 1/2 (CINV1/2) irreversibly catalyzes Suc into glucose (Glc) and fructose (Frc) (Barratt et al, 2009). Here, we utilized the loss-of-function mutant of CINV1/2, cinv1/2 (sugar signaling/metabolism mutant [Barratt et al, 2009;Meng et al, 2021]), to obtain the endogenous sugars of genetic manipulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cotyledon greening of etiolated seedlings was promoted by endogenous sugars Cytosolic invertase 1/2 (CINV1/2) irreversibly catalyzes Suc into glucose (Glc) and fructose (Frc) (Barratt et al, 2009). Here, we utilized the loss-of-function mutant of CINV1/2, cinv1/2 (sugar signaling/metabolism mutant [Barratt et al, 2009;Meng et al, 2021]), to obtain the endogenous sugars of genetic manipulation.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 1 mL of the reverse transcription reaction was used as template for PCR amplification. The same RNA samples and primers were used for real-time PCR analysis that was performed and statistically analyzed as described (Meng et al, 2021). Kinetic detection of PCR products using Sybrgreen real-time RT-PCR.…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…PtrA/NINV7 was prominently upregulated by cold stress, indicating that it is a cold‐responsive gene. It is well accepted that TFs play a key role in transcriptional regulation of stress‐responsive genes through interacting with the corresponding cis ‐acting elements (CAEs) in the promoters (Li et al ., 2020; Meng et al ., 2020, 2021). In the current study we showed that the A/T‐rich sequences in the MAR region of the promoter are essential for the cold‐induced activation of PtrA/NINV7 , implying that the A/T‐rich sequences may also act as a CAE for orchestrating gene expression in response to cold cues.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, flowering is a physiological development process that transforms plants from vegetative growth to reproductive growth, which indicates that miR156/ SPL participates in the regulation of plant age. Exogenous sugars trigger the Arabidopsis juvenile-to-adult phase transition via a miR156A/ SPL module [ 44 ]. Fraxinus mandshurica is a perennial woody plant.…”
Section: Discussionmentioning
confidence: 99%